Life Cycle Assessment of Solid Waste Management in Düzce Province within the Scope of Türkiye’s Decarbonization Policies - Kadriye Elif Maçin (Doğal Afetler ve Çevre Dergisi, 2025)
This study evaluates the environmental impacts of solid waste management in Düzce within the framework of Türkiye's 2053 carbon decarbonization target. Using the life cycle assessment, the effects of different electricity mixes were compared. The annual waste generation in Düzce was defined as the functional unit, and the ReCiPe-2016 method was employed to analyze eight impact categories across seven different scenarios. Background data were sourced from literature and the ecoinvent 3.7.1 database. Additionally, sensitivity analysis was conducted to assess variations in gas collection rates at landfill. The findings indicate that despite Türkiye's efforts to achieve carbon neutrality by 2053, failure to meet the zero-waste-to-landfill target could lead to additional environmental burdens. Key concerns include low recycling rates, insufficient energy recovery, and long-term environmental risks posed by biodegradable waste disposal. Raw material substitution by recycling provide environmental benefits across all scenarios, emphasizing the need for the swift implementation of the deposit system, which has gained prominence in recent years. Integrating a circular economy model into waste management is significant for ensuring compliance with decarbonization policies. Strengthening public-private partnerships and optimizing logistics processes are essential strategic measures. Furthermore, conducting cost analyses in waste management will support policymakers in developing effective policy recommendations.